2023
DOI: 10.7759/cureus.40467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Smear Layer Removal of Human Teeth Root Canals Using Herbal and Chemical Irrigants: An In Vitro Study

Mridusmita Mukherjee,
Tribisha Kalita,
Pranamee Barua
et al.

Abstract: Objectives Over many years, many intracanal irrigants have removed smear layers during routine root canal therapy. The efficacies of conventional endodontic chemical irrigants are documented, but limited research is available on herbal irrigants' role in the endodontic therapy irrigation protocol. This study aimed to evaluate endodontic irrigants' smear layer removal efficacy, namely, 3% sodium hypochlorite (NaOCl), 17% ethylenediaminetetraacetic acid (EDTA), green tea extract, and Triphala extract,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Many other studies on various other herbal agents used as an endodontic irrigation solution were found to be effective in removing the smear layer. Mukherjee et al [ 24 ] concluded that Triphala is as effective as EDTA in removing the smear layer from root canals during endodontic procedures. Sharma and Dhawan [ 22 ] examined the smear layer removal performance of green tea extract, tulsi leaf extract, and neem leaf extract compared with sodium hypochlorite.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies on various other herbal agents used as an endodontic irrigation solution were found to be effective in removing the smear layer. Mukherjee et al [ 24 ] concluded that Triphala is as effective as EDTA in removing the smear layer from root canals during endodontic procedures. Sharma and Dhawan [ 22 ] examined the smear layer removal performance of green tea extract, tulsi leaf extract, and neem leaf extract compared with sodium hypochlorite.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is essential to acknowledge that the capacity of these herbal irrigants in removing the smear layer is relatively lower compared to chelating agents such as ethylenediaminetetraacetic acid (EDTA) and tetracycline antibiotics (MTAD, a combination of a tetracycline isomer, an acid, and a detergent)[ 50 , 51 ]. However, certain studies have reported that natural irrigants can effectively remove the smear layer while causing minimal harm to the mechanical and chemical properties of radicular dentin in contrast to synthetic agents, as they have a less detrimental impact on dentin's mechanical properties[ 52 ].…”
Section: Herbal Extractsmentioning
confidence: 99%
“…2023, 13, 11728 2 of 10 dentin [7,8]. The number and diameter of the dentinal tubules are known to be the most important factors affecting dentin hypersensitivity [9][10][11][12]. In addition, the number of dentinal tubules per area is reportedly higher in teeth with hypersensitivity and the diameter is twice that of normal teeth [13].…”
Section: Introductionmentioning
confidence: 99%